A class of sulfonamides as carbonic anhydrase I and II inhibitors. (2nd November 2016) - Gokcen, Taner; Gulcin, Ilhami; Ozturk, Turan; Goren, Ahmet C.
Abstract: Four groups of novel sulfonamide derivatives: (i) acetoxybenzamide, (ii) triacetoxybenzamide, (iii) hydroxybenzamide and (iv) trihydroxybenzamide, all having thiazole, pyrimidine, pyridine, isoxazole and thiadiazole moieties were prepared and their inhibitory effects were studied on two metalloenzymes, i.e. carbonic anhydrase isozymes (hCA I and II), purified from human erythrocyte cells by Sepharose-4B-l -tyrosine-sulfanilamide affinity chromatography. These enzymes are present in almost all living organisms to catalyse the synthesis of bicarbonate ion (HCO3 − ) from carbon dioxide and water. The sulfonamide derivatives were found to be active against hCA I and II in the range of 2.62–136.54 and 5.74–210.58 nM, respectively.